Association of dietary index of gut microbiota with cardiovascular disease risk: new evidence from NHANES 2007–2018 - Jiameng Jin; Xingang Sun; Lihong Wang (BMC Cardiovascular Disorders)
Abstract Background The dietary index of gut microbiota (DI-GM) is a newly proposed index for assessing dietary quality, and studies on its association with cardiovascular disease (CVD) are limited. This study aimed to investigate the association between DI-GM and the prevalence of CVD. Methods We utilized data from the National Health and Nutrition Examination Survey (NHANES). Logistic regression analyses were performed to examine the association between DI-GM and CVD. Smoothed curve fitting was employed to explore potential nonlinear relationships. Additionally, subgroup analyses were conducted to assess the stability of the results. Results The study included 22,590 participants, of whom 20,216 had no CVD and 2,374 had CVD. After adjusting for all covariates, the DI-GM score was significantly negatively associated with CVD risk, with a 4% reduction in CVD risk for each unit increase in DI-GM score (OR = 0.96, 95% CI: 0.94–0.99, P = 0.015). Notably, the highest DI-GM score group (6–12) had a 13% lower risk of CVD compared to the lowest DI-GM score group (0–3) (OR = 0.87, 95% CI: 0.76-1.00, P = 0.048). Conclusion The research results indicate that a higher DI-GM score protects against CVD, providing crucial empirical support for dietary intervention strategies based on gut microbiota modulation. Clinical trial number Not applicable.